Embracing My Body: Unveiling the Diversity in Body Appreciation among Clustered Groups of Filipina Emerging Adults - Neves, Aerin Paulina B.; Padama, Angela Marie D.; Malgapu, Mia Gayle S.; Golosino, Benecia Loyd V.; Arcinas, Myla M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study examines the body appreciation levels of clustered groups of Filipinas emergent adult in Metro Manila based on their socio-demographic characteristics (SDCs), body esteem (BE), quality of relationship with their parents (QRP), and quality of interactions with their peers (QIP). Using a purposive non-probability sampling technique, 227 Filipina emerging adults between 18 and 29 from Metro Manila participated in the study. The data was collected through an online survey using a semi-structure questionnaire. Mann-Whitney U-test and Kruskal-Wallis were used to determine the significant difference between clustered groups. Findings show that young Filipinas emerging adults have higher BA levels; college undergraduates have higher BA levels; there is no significant difference in BA levels between income groups; those with high BE have higher BA; those with poor QRP have higher BA; there is no significant difference in BA levels between excellency groups. In conclusion, a statistically significant difference exists between the BA levels of the aggregated categories of BE, QRP, EA, and age. To further examine the body appreciation of Filipina emerging adults, a blended method study can provide depth to the findings generated using the quantitative study.